2015
DOI: 10.1007/s00268-015-3034-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Simultaneous Resection of Colorectal Primary Tumor and Liver Metastases: Results of a Multicenter International Study

Abstract: Our combined data show that in experienced centers, simultaneous laparoscopic approach is technically feasible, safe, and associated with good oncological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 94 publications
4
56
2
6
Order By: Relevance
“…This complication rate was not different from the rates reported in large series of isolated colorectal resections [39] or open combined resections [11]. In addition, they found that ASA score C3 and global operative time were independent predictors of postoperative complications [21]. Even in the comparative study between totally laparoscopic and totally open combined resections by Jung et al [22], a significant advantage in terms of postoperative events was not found in patients scheduled for minimally invasive approach, in spite of a trend toward reduced morbidity rate (17 vs 42 % in open group).…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…This complication rate was not different from the rates reported in large series of isolated colorectal resections [39] or open combined resections [11]. In addition, they found that ASA score C3 and global operative time were independent predictors of postoperative complications [21]. Even in the comparative study between totally laparoscopic and totally open combined resections by Jung et al [22], a significant advantage in terms of postoperative events was not found in patients scheduled for minimally invasive approach, in spite of a trend toward reduced morbidity rate (17 vs 42 % in open group).…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, more recently even safety and efficacy of combined resections have been reported [7][8][9][10][11], with shorter length of stay and reduced morbidity compared with staged approaches if performed in a selected population of patients [6][7][8]. Although the debate regarding the optimal timing for resection of SCLM is still open [6][7][8], mainly because of concerns regarding a presumptive higher frequency of colonic anastomosis leakage, even combined, totally laparoscopic approach for CRC and SCLM is experiencing a growing trend [21][22][23][24].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All centers involved in this study have more than 4 years of experience in the liver and colorectal laparoscopic surgical field, and characteristics of patients involved in this database were previously reported [27]. Those laparoscopic patients were compared to all consecutive patients that underwent open liver resection with combined open resection of CRC and SCRLM at Mauriziano Umberto I (Turin, Italy) and at Saint Antoine Hospital (Paris, France) during the study period.…”
Section: Patient Selectionmentioning
confidence: 99%